Principales insectos plagas en el cultivo de girasol (Helianthus annuus)” en los predios de la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Babahoyo - Rodríguez Nivelo, José Luis (2020)
The research work was carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo with the aim of obtaining knowledge about the presence of the main insects that affect the sunflower crop that is planted and produced in this faculty, recognize the damage caused by insects that affect sunflower cultivation in this agricultural area of Los Ríos Province, identify which controls are carried out. Within the general methods that were applied to the study, deductive and inductive methods were used in this research, since the hypotheses were raised and verified throughout the development of the research in order to reach the conclusions and recommendations of the work. In the evaluation carried out in the three main physiological stages of cultivation at the Faculty of Agricultural Sciences, it was found that the number of insects that affect the sunflower cultivation is considered to be in a range of light damage, among which the following were identified: tracers , miners, borers and leaf / seed eaters, for which technical measures are carried out to control them, carrying out all the phytosanitary practices from the evaluation in the field by the students together with their teachers to the selection of the insecticides that were used in the moment the insect damage to the crop was presented. It is important to mention that a respective documentation is made of the types of insecticides that will be used in order to avoid insect resistance in the sunflower crop.